(3HOjYjI GdSjOI YGFTI HfJ jhSa GdHGYhfis - (3YGFTI HfJ jhSa GdHGYhfjI,J (B922 (3g` s ((3YeQ CfSi Hf eMeO OjH GdUbYGf GdHjQhJi s)
(3ChdgG (B:s
(3ai MSf eWdY CbeGQ HPi Sde CUHMJ ai ReQI GdYTGb cGdYde s
(3BNQgG (B:s
(3eOMJ eLOc hGdENdGU edJRe ajg hMSf QLGFi ajc eNJJei s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B6 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B436s
Keywords: (3GdHdGZIs